Penurunan Non Revenue Water (NRW) melalui Analisis Neraca Air dan Indikator Kinerja pada Wilayah Pelayanan Pilang Raya Perumda Air Minum Tirta Giri Nata Kota Cirebon - Fathani, Aghfiranisa; Masduqi, Ali; Hastuti, Dian Suci (Universitas Tanjungpura, 2025)
Perumda Air Minum Tirta Giri Nata Kota Cirebon as BUMD with healthy performance and has Full Cost Recovery (FCR), but has a high NRW value of 37.97% in 2023. Based on the monthly distribution report during February 2024 - April 2024, the location with the highest leakage report is the Pilang Raya service area with 8 leakage reports. This research was conducted using water balance analysis method and performance indicators to formulate NRW reduction strategy in Pilang Raya service area. NRW in the period May 2023 - April 2024 amounted to 54.37% with a very large water volume of 327,152 m3/12 months. Annual water loss during this period is 52.37% with a volume of water loss of 315,121 m3/12 months. The physical water loss is 46.64% and non-physical water loss is 5.73%. If converted into cost value, the potential loss of revenue due to annual physical water loss is Rp 2,051,523,612, - and annual non-physical water loss is Rp 252,209,424, -. Physical water loss is classified as category D (extraordinary waste of resources). ATR indicator performance is classified as category D (highly inefficient). The NRW reduction program strategy is developed based on the results of the water balance analysis and performance indicators adjusted to Perumda's business plan.